The human otubain2-ubiquitin structure provides insights into the cleavage specificity of poly-ubiquitin-linkages - Altun, M; Walter, T; Kramer, H; Herr, P; Iphöfer, A; Boström, J; David, Y; Komsany, A; Ternette, N; Navon, A; Stuart, D; Ren, J; et al. (Public Library of Science, 2015)
Ovarian tumor domain containing proteases cleave ubiquitin (Ub) and ubiquitin-like polypeptides from proteins. Here we report the crystal structure of human otubain 2 (OTUB2) in complex with a ubiquitin-based covalent inhibitor, Ub-Br2. The ubiquitin binding mode is oriented differently to how viral otubains (vOTUs) bind ubiquitin/ISG15, and more similar to yeast and mammalian OTUs. In contrast to OTUB1 which has exclusive specificity towards Lys48 poly-ubiquitin chains, OTUB2 cleaves different poly-Ub linked chains. N-terminal tail swapping experiments between OTUB1 and OTUB2 revealed how the N-terminal structural motifs in OTUB1 contribute to modulating enzyme activity and Ub-chain selectivity, a trait not observed in OTUB2, supporting the notion that OTUB2 may affect a different spectrum of substrates in Ub-dependent pathways.